2012
DOI: 10.1111/j.1365-3083.2012.02724.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Toll‐Like Receptor 3 in Spleen is Associated with Experimental Arthritis in Rats

Abstract: This study is to investigate the regulation of Toll-like receptor (TLR) expression in systemic immune reactions in different arthritis rat models, which will provide evidence to understand the mechanisms of rheumatoid arthritis further. Arthritis-susceptible DA rats were used to induce arthritis by pristane or collagen type II, and TLR2, 3, 4 and 7 expression levels in spleen were detected by real-time quantitative polymerase chain reaction. TLR3 mRNA expression in spleen of both collagen-induced arthritis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…TLR3, like other TLRs, has long been considered remarkably conserved across the taxonomic kingdoms and constitutively expressed by numerous immune cells [13], even though studies on regulation of the TLR3 signaling pathway have been widely performed [11,14-16]. Our study and others have shown that TLR3 expression per se changes dramatically under certain scenarios and regulation to its expression is a means to prevent the excess production of proinflammatory cytokines from its overactivated signaling pathway.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…TLR3, like other TLRs, has long been considered remarkably conserved across the taxonomic kingdoms and constitutively expressed by numerous immune cells [13], even though studies on regulation of the TLR3 signaling pathway have been widely performed [11,14-16]. Our study and others have shown that TLR3 expression per se changes dramatically under certain scenarios and regulation to its expression is a means to prevent the excess production of proinflammatory cytokines from its overactivated signaling pathway.…”
Section: Introductionmentioning
confidence: 64%
“…The activated TLR3 pathway could further promote RASFs sustaining B cell activation in the synovium [9]. In the previous study, we found that both TLR3 mRNA and protein expressions are prominently upregulated in splenic macrophages in rats with pristine-induced arthritis (PIA) and collagen-induced arthritis (CIA), and downregulation of TLR3 expression modulates the severity of arthritis [10,11]. TLR3 in the synovium of PIA rats is also overexpressed in an early and persistent style and the activation of the TLR3 signaling pathway in vivo could aggravate PIA [12].…”
Section: Introductionmentioning
confidence: 99%
“…And the ability of dsRNA triggering arthritis was related to the function of macrophage secreting type I interferon, and also depended on type I interferon signaling [15]. Our previous studies also showed that PIA in rats relied on TLR3 and its downstream cytokines [4,17]. TLR3 ligands were shown to stimulate DC from RA patients to secrete IL-12, MIF [10,18].…”
Section: Introductionmentioning
confidence: 88%
“…A significant TLR3 up-regulation has been observed in splenocytes in the rat pristane-induced arthritis (PIA) model upon pristane treatment and stimulation of TLR3 with poly-I:C. Accordingly, TLR3 inhibition by using small interfering RNA (siRNA) ameliorated RA in this animal model [111]. The treatment with methotrexate (MTX) inhibited RA symptoms and induced TLR3 over-expression in splenocytes from PIA and collagen-induced arthritis (CIA) rat models [112]. Contrasting data emerged from the study conducted by Yarilina and colleagues [113], where it was demonstrated that TLR3 activation inhibited arthritis in CIA and K/BxN serum transfer models.…”
Section: Rheumatoid Arthritismentioning
confidence: 97%